Evaluasi Kinerja Pencahayaan Alami Pada Ruang Kerja (Studi Kasus: Program Studi Arsitektur Universitas Nusa Cendana) - Hendrik, Maria Lady (JARI: Journal of Architecture, Research and Innovation, 2024)
Natural lighting is essential for creating a comfortable and productive work environment, impacting both physical and mental health. Office spaces like those used for writing and reading require optimal visual comfort. This study evaluates the performance of natural lighting in the lecturer's room of the Architecture Department. Methods included measuring light intensity and using DIALux EVO software for light distribution simulations Results show that light distribution is crucial for preventing visual discomfort. Measurements indicate that light intensity in the work area reaches 2000 lux in the morning but drops to 13 lux in the afternoon, especially at desks facing north. These levels do not meet SNI standards for natural lighting in workspaces. Additionally, findings reveal that vertical blinds significantly enhance light distribution an uniformity within the room